GOVERNANCE OF TARUSAN KAMANG MAGIC POND AS A HALAL DESTINATION IN AGAM DISTRICT - RAHMAN HIDAYU; ERWIN ERWIN; AFRIZAL AFRIZAL (Universitas Islam Negeri Imam Bonjol Padang, 2022)
The Tarusan Kamang Magical Lake is a future tourist attraction that has the potential to implement halal tourism. This study aims to see whether there is conformity in the arrangement of tourist objects with the principles of halal tourism. The method used is field research, where the researcher directly observes the research object. The study results show that the Tarusan Kamang Magic Lake fulfills seven out of fifteen indicators of halal tourism. The improvements that can be made include: 1) The local government is managing tourist objects so that they can build halal restaurants with polite-looking servers by Islamic ethics; 2) Building a prayer room to make it easier for tourists to worship, 3) Providing halal tourism education to the public or tourism managers to improve Islamic ethics and be able to separate tour guides based on gender; 4) Holding Islamic festivals such as breaking the fast together in the month of Ramadan and involving tourists in these activities.